Public speaking : concepts and skills for a diverse society - Jaffe, Clella Iles , 1944- (Boston, Massachusetts : Wadsworth Cencage Learning, 2013)
PUBLIC SPEAKING is a culturally informed book that never loses sight of its fundamental purpose: to train students to be effective public speakers and listeners in a world filled with monumental cultural, political, and technological changes. It applies 2,500-year-old principles with up-to-date research into concepts, skills, theories, applications, and critical thinking proficiencies essential for listening and speaking in today's world. Its discussions of classic public speaking topics are all grounded in an awareness of the impact of cultural nuances--ranging from gender differences to co-cultures within the United States to the traditions of other nations. This provides speakers with a heightened awareness of and sensitivity to the audience
1. Introduction to public speaking and culture -- 2. Giving your first speech: developing confidence -- 3. Ethics in a diverse society -- 4. Effective listening -- 5. Selecting your topic and purpose -- 6. Audience analysis -- 7. Researching your speech in the digital age -- 8. Choosing supporting materials -- 9. Organizing your main points -- 10. Introductions and conclusions -- 11. Outlining your speech -- 12. Choosing effective language -- 13. Presentation aids -- 14. Delivering your speech -- 15. Telling narratives -- 16. Informative speaking -- 17. Foundations of persuasion -- 18. Persuasive speaking
Includes bibliographical references (p. 375-390) and index
Keywords: Multiculturalism; Public speaking